XPS analysis of genomic DNA adsorbed on PEI‐modified surfaces. (11th January 2016) - Vanzetti, Lia; Pasquardini, L.; Potrich, C.; Vaghi, V.; Battista, E.; Causa, F.; Pederzolli, C.
Abstract : Polyethylenimine (PEI) is a cationic polymer able to interact with nucleic acids. Taking advantage of this property, PEI‐modified functional surfaces for the capture of DNA were developed and characterized with X‐ray photoelectron spectroscopy (XPS) during every step of the preparation. The XPS demonstrated the presence of PEI on the functional surfaces, while the density of PEI primary amino groups was quantified with a colorimetric test, resulting in 6 × 10 14 amino groups/cm 2 . Different amounts of DNA were adsorbed on the functional surfaces, and the interaction between DNA and PEI was monitored both via fluorescence and XPS. The functional surfaces were indeed able to capture DNA, opening the possibility of a low‐cost and fast strategy for the purification of DNA. Copyright © 2016 John Wiley & Sons, Ltd.